2009
DOI: 10.1136/gut.2008.168534
|View full text |Cite
|
Sign up to set email alerts
|

Human adult stem cells derived from adipose tissue protect against experimental colitis and sepsis

Abstract: hASCs emerge as key regulators of immune/inflammatory responses in vivo and as attractive candidates for cell-based treatments for IBD and sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

49
543
8
17

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 588 publications
(617 citation statements)
references
References 32 publications
49
543
8
17
Order By: Relevance
“…IL-1b-primed MSCs attenuate the development of DSS-Induced colitis Similar to previous reports, 27,28 we successfully induced colitis in C57BL/6 mice by oral administration of 3% DSS. The mouse colitis was characterized by sustained bloody diarrhea, weight loss, 100% mortality at day 11 ( Figure 2a, b and d), shorter and lighter colons (Figure 2c), histological changes with severe colonic transmural inflammation, increased wall thickness, localized inflammatory cell infiltration, epithelial ulceration with degeneration of crypt architecture and loss of goblet cells (Figure 2e and f).…”
Section: Resultssupporting
confidence: 81%
“…IL-1b-primed MSCs attenuate the development of DSS-Induced colitis Similar to previous reports, 27,28 we successfully induced colitis in C57BL/6 mice by oral administration of 3% DSS. The mouse colitis was characterized by sustained bloody diarrhea, weight loss, 100% mortality at day 11 ( Figure 2a, b and d), shorter and lighter colons (Figure 2c), histological changes with severe colonic transmural inflammation, increased wall thickness, localized inflammatory cell infiltration, epithelial ulceration with degeneration of crypt architecture and loss of goblet cells (Figure 2e and f).…”
Section: Resultssupporting
confidence: 81%
“…Previous studies have demonstrated that mesenchymal stem cells (MSCs) are able to regulate the immune system, and MSCs have been used to treat a range of conditions, including acute lung injury, inflammatory bowel disease, graft versus-host reactions and ischemic heart disease (7,8). Previous attempts have been made to treat sepsis using MSCs, and MSCs have been successfully used in animals to inhibit the systemic inflammation reaction through interleukin (IL)-10, and thereby relieve the functional impairment, which is associated with sepsis and endotoxemia (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…On a déjà utilisé des cellules allogéniques non appariées dans des applications cliniques; 8 des cellules xénogéniques ont même été utilisées avec succès dans des modèles précliniques immunocompétents. 9 On a attribué cette capacité remarquable des CSM à échapper à la détection du système immunitaire du receveur à l'absence d'un complexe majeur d'histocompatibilité de classe II et de molécules co-stimulantes nécessaires à la reconnaissance des cellules hôtes T CD4?. 10 Le statut 'immunoprivilégié' des CSM est important d'un point de vue clinique.…”
Section: Que Sont Les Cellules Stromales Mésenchymateuses?unclassified
“…Mismatched allogeneic cells have been used clinically, 8 and even xenogeneic cells have been used successfully in immunocompetent preclinical models. 9 This remarkable ability of MSCs to evade detection by the recipient's immune system has been attributed to the lack of major histocompatibility complex class II and co-stimulatory molecules necessary for host CD4? T cell recognition.…”
mentioning
confidence: 99%